Intersectional socioeconomic disparities in continuous smoking through pregnancy among pre-pregnant smokers in Sweden between 2006 and 2016 - Sten Axelsson Fisk; Jannike Cassel; Mikael Rostila; Can Liu; Sol Pia Juárez (BMC, 2024)
Abstract Background While well-established associations exist between socioeconomic conditions and smoking during pregnancy (SDP), less is known about social disparities in the risk of continuous SDP. Intersectional analyses that consider multiple social factors simultaneously can offer valuable insight for planning smoking cessation interventions. Methods We include all 146,222 pregnancies in Sweden between 2006 and 2016 where the mother smoked at three months before pregnancy. The outcome was continuous SDP defined as self-reported smoking in the third trimester. Exposures were age, education, migration status and civil status. We examined all exposures in a mutually adjusted unidimensional analysis and in an intersectional model including 36 possible combinations. We present ORs with 95% Confidence Intervals, and the Area Under the Curve (AUC) as a measure of discriminatory accuracy (DA). Results In our study, education status was the factor most strongly associated to continuous SDP among women who smoked at three months before pregnancy. In the unidimensional analysis women with low and middle education had ORs for continuous SDP of 6.92 (95%CI 6.63-7.22) and 3.06 (95%CI 2.94-3.18) respectively compared to women with high education. In the intersectional analysis, odds of continuous SDP were 17.50 (95%CI 14.56-21.03) for married women born in Sweden aged ≥ 35 years with low education, compared to the reference group of married women born in Sweden aged 25-34 with high education. AUC-values were 0.658 and 0.660 for the unidimensional and intersectional models, respectively. Conclusion The unidimensional and intersectional analyses showed that low education status increases odds of continuous SDP but that in isolation education status is insufficient to identify the women at highest odds of continuous SDP. Interventions targeted to social groups should be preceded by intersectional analyses but further research is needed before recommending intensified smoking cessation to specific social groups.